Translation and the question of cultural identity in a post-colonial context : the model of literary translation from Arabic into English and French - Branki, Ourida; Sebihi, Mohamed Lakhdar (Journal of Human Sciences, 2023)
Literary Translation, as a cultural practice, contributes in constructing new cultural identities, for it has the power to convey an image of the foreign cultures (source culture) to the local culture (target culture), which is known in post-colonial translation theory as cultural representation. However, Translation, in a post colonial context, raises the problem of power imbalance between languages /cultures of the West and those of the Orient, and thus the problem of cultural hegemony. That being said, this article aims to shed the light on the ideological, political and socio-cultural dimensions of post-colonial translation through tackling the model of translating Arab literature into hegemonic Western languages, namely French and English. It also attempts to highlight the role of translation in maintaining or deconstructing stereotypes about the other.